Fintech Effect, Fintech Implementation and Fintech Peer-To-Peer Lending Credit Risk Management on MSMe Financing Distribution - Retno Suliati Suleiman; Tresea Lestari; Ahmad Fahrian Aditya (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze the effect of fintech, fintech implementation, and fintech peer-to-peer lending credit risk management on the distribution of financing to MSMEs. This study uses quantitative methods, and survey methods as data collection techniques. The results of this study are based on hypothesis testing, it can be seen that the influence of fintech, fintech implementation, and fintech p2p lending credit risk management simultaneously has an influence on the distribution of MSME financing, which means there is a positive influence. This means that the existence of fintech among the community, especially MSME actors, can make it easier for MSME actors in terms of transaction speed and ease of use, making fintech believed to be able to help their business development. However, if partially based on the results of the hypothesis test, the influence of fintech does not affect the distribution of UMKM financing, which means that there is a negative effect. The implementation of fintech is based on the results of the hypothesis test that there is a partially positive effect on the distribution of UMKM financing and based on the results of the hypothesis test of fintech credit risk management, there is a partial positive effect on the distribution of MSME financing.